1999
DOI: 10.1177/000348949910800504
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotics in Chronic Suppurative Otitis Media: A Bacteriologic Study

Abstract: Conservative medical management of chronic suppurative otitis media (CSOM) is an important step in achieving a dry ear. Topical antibiotic ear drops and aural toilet form the mainstay of medical management of noncholesteatomatous CSOM. This study analyzes the causal organisms and their sensitivity to various antibiotics. Out of 382 swabs examined, the major organisms isolated were Pseudomonas aeruginosa (27.2%), followed by Staphylococcus aureus (23.6%). The sensitivity of P. aeruginosa was 100% to ceftazidime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
28
2
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(45 citation statements)
references
References 21 publications
13
28
2
2
Order By: Relevance
“…Results of the present study showed P. aeruginosa and S. aureus as the most common isolates from active CSOM infections. This is in tandem with the observations made by many other authors [1,10,11,12]. Coagulase negative Staphyloccoccus spp.…”
Section: Discussionsupporting
confidence: 90%
“…Results of the present study showed P. aeruginosa and S. aureus as the most common isolates from active CSOM infections. This is in tandem with the observations made by many other authors [1,10,11,12]. Coagulase negative Staphyloccoccus spp.…”
Section: Discussionsupporting
confidence: 90%
“…Observations by Indudharan et al [18] are similar to Yuen et al [17] who reported the presence of P. aeruginosa (27.2%) and S. aureus (23.6%) in their study population. Pseudomonas showed total sensitivity (100%) to ciprofloxacin; significant sensitivity (95.4%) was shown toward polymyxin B.…”
Section: Discussionsupporting
confidence: 84%
“…Similarly, Poorey & lyer 15 isolated Pseudomonas in 35.2% ears. Pseudomonas was also isolated as the predominant organism by Maji PK et al 16 (63.8%), Kumar S et al 17 (45.9%) and lndudharan R et al 18 (27.2%).…”
Section: Resultsmentioning
confidence: 92%